Standard assessments of frailty are validated predictors of mortality in hospitalized patients with cirrhosis. Issue 2 (28th April 2015) - Tapper, Elliot B.; Finkelstein, Daniel; Mittleman, Murray A.; Piatkowski, Gail; Lai, Michelle
<x xml:space="preserve">Abstract</x> The risk of morbidity and mortality for hospitalized patients with cirrhosis is high and incompletely captured by conventional indices. We sought to evaluate the predictive role of frailty in an observational cohort study of inpatients with decompensated cirrhosis between 2010 and 2013. The primary outcome was 90‐day mortality. Secondary outcomes included discharge to a rehabilitation hospital, 30‐day readmission, and length of stay. Frailty was assessed with three metrics: activities of daily living (ADL), the Braden Scale, and the Morse fall risk score. A predictive model was validated by randomly dividing the population into training and validation cohorts: 734 patients were admitted 1358 times in the study period. The overall 90‐day mortality was 18.3%. The 30‐day readmission rate was 26.6%, and the rate of discharge to a rehabilitation facility was 14.3%. Adjusting for sex, age, Model for End‐Stage Liver Disease, sodium, and Charlson index, the odds ratio for the effect of an ADL score of less than 12 of 15 on mortality is 1.83 (95% confidence interval [CI] 1.05‐3.20). A predictive model for 90‐day mortality including ADL and Braden Scale yielded C statistics of 0.83 (95% CI 0.80‐0.86) and 0.77 (95% CI 0.71‐0.83) in the derivation and validation cohorts, respectively. Discharge to a rehabilitation hospital is predicted by both the ADL (<12) and Braden Scale (<16), with respective adjusted odds ratios of 3.78 (95% CI 1.97‐7.29) and 6.23 (95% CI 2.53‐15.4). Length of stay was associated with the Braden Scale (<16) (hazard ratio = 0.63, 95% CI 0.44‐0.91). No frailty measure was associated with 30‐day readmission. Conclusions: Readily available, standardized measures of frailty predict 90‐day mortality, length of stay, and rehabilitation needs for hospitalized patients with cirrhosis. (Hepatology 2015;62:584–590